PENGUATAN PENGELOLAAN BACK OFFICE E-COMMERCE UNTUK PENINGKATAN KAPASITAS UKM DI KOTA SAMARINDA - Muhammad Zaini; Riyadi Riyadi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The low business capacity of SMEs is the result of the majority of SMEs (93.33%) still being managed traditionally. The limited capacity of SMEs can be overcome if SMEs are willing and able to change the way their business is managed, which is still traditionally replaced with web-based information technology, which is able to manage business and transaction processing without limits on space and time, such as the Prestashop back office application system. This application provides 2 types of modules, namely Back Office which consists of purchasing, sales, inventory, cash and bank modules, Front Office which functions as cash sales, so it is very easy to use by SMEs.